Association between Smoking and 30-Day Outcomes in Otologic Surgery. (January 2020) - Kay-Rivest, Emily; Mascarella, Marco; Sewitch, Maida J.; Cloutier, François; Mijovic, Tamara
Objective: To determine the effect of current smoking status on 30-day postoperative adverse events in patients undergoing otologic surgery. Study Design: Retrospective cohort study. Setting: Database of the American College of Surgeons National Surgical Quality Improvement Program from 2006 to 2016. Subjects and Methods: Adult patients undergoing middle ear and mastoid surgery were included. Preoperative smoking status was determined, and adverse events within 30 days of surgery were recorded. Descriptive statistics were used to characterize the study sample. Multivariable logistic regression was performed to identify the association between sociodemographic and clinical variables and postoperative adverse events. Population-attributable fractions were then calculated. Results: A total of 10, 684 patients who underwent otologic surgery were included, of whom 2036 (19.1%) were smokers. The most commonly performed surgery was tympanoplasty with and without ossicular chain reconstruction, followed by canal wall up tympanomastoidectomy. Adverse events occurred in 221 (2.1%) patients; the most common was superficial wound infections (n = 99, 0.9%). In smokers, the odds ratio for any adverse event was 1.97 (95% CI, 1.42-2.71). The odds ratios (95% CIs) for superficial wound infections, wound dehiscence, and 30-day readmission among smokers were 1.89 (1.32-2.86), 3.92 (1.26-11.60), and 1.84 (1.15-2.87), respectively. The population-attributable fraction for any adverse event in smokers was 15.5%. Conclusions: In patients undergoing otologic surgery, smokers are more likely than nonsmokers to have postoperative adverse events—in particular, wound infections, wound dehiscence, and readmission to hospital.